2007
DOI: 10.1146/annurev.psych.57.102904.190200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Diagnosis of Personality Disorder: Perennial Issues and an Emerging Reconceptualization

Abstract: This chapter reviews recent (2000)(2001)(2002)(2003)(2004)(2005) personality disorder (PD) research, focusing on three major domains: assessment, comorbidity, and stability. (a) Substantial evidence has accrued favoring dimensional over categorical conceptualization of PD, and the five-factor model of personality is prominent as an integrating framework. Future directions include assessing dysfunction separately from traits and learning to utilize collateral information. (b) To address the pervasiveness and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
726
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 702 publications
(768 citation statements)
references
References 187 publications
(143 reference statements)
33
726
1
8
Order By: Relevance
“…This approach reflects increasing evidence for the validity of dimensional over categorical approaches to personality pathology. 11 Although the lack of consistent personality differences in the literature suggests that women with PD and BN may share similar anxious and impulsive personality traits, evidence for differential associations between these traits and eating disorder features may reflect distinctions between the disorders with important treatment implications.…”
Section: Introductionmentioning
confidence: 99%
“…This approach reflects increasing evidence for the validity of dimensional over categorical approaches to personality pathology. 11 Although the lack of consistent personality differences in the literature suggests that women with PD and BN may share similar anxious and impulsive personality traits, evidence for differential associations between these traits and eating disorder features may reflect distinctions between the disorders with important treatment implications.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies have tried to capture PDs using a large variety of instruments in normal and clinical samples [4][5][6][7] ; however, at the moment there is still no consensus on one particular dimensional model to assess PDs. However, Clark 1 suggested the use of the FFM or some variant of the FFM because it has acquired the status of a reference model for the description of normal personality traits and is widely accepted.…”
mentioning
confidence: 99%
“…However, this percentage reflects the number of individuals who sought treatment and received a diagnosis for a PD; it does not include the individuals who do not seek help but are afflicted with a PD. Research shows that PDs are associated with reduced quality of life and dysfunction in almost every area with which health care providers are concerned (Clark, 2007) and therefore should be accorded the most effective and efficient diagnostic model and treatment options possible.…”
Section: Personality Disordersmentioning
confidence: 99%
“…The categorical approach is currently the 8 approach used by clinicians and has been since its original publication in 1980; however, empirical evidence has been collecting for decades showing that the structure of PDs can better be described using a dimensional approach (Clark, 2007). One survey reports that 74% of experts think the DSM-IV-TR categorical model of PDs should be replaced, 87% believe personality pathology is dimensional in nature, and 70% indicated that a hybrid model of PDs is the most desirable alternative to the categorical model (Morey et al, 2014).…”
Section: Current Debatementioning
confidence: 99%